Influence polysulphide-enriched garlic supplementation lowers blood pressure in healthy adults following high-intensity constant load exercise. / Alif Nazrin Jumat ...[ et al.] - Jumat, Alif Nazrin; Nordin, Ahmad Safwanudin; Norhamazi, Iqbal Khan; Mud Puad, Sharifah Maimunah; Linoby, Adam (Universiti Teknologi MARA, 2021)
This study aim is to determine the effects of short-term polysulfide-enriched garlic (PEG) on resting blood pressure (BP) and physiological responses to continuous, high-intensity exercise in collegiate-level athletes. Twelve collegiate-level male athletes underwent a randomized, double blind, crossover, placebo-controlled trial of PEG and PLA (placebo) supplementation, with a washout period of 14-day separating each trial. Following a 4-day supplementation of 4 g PEG and PLA (placebo), participants consumed a single dose of the supplement 3 hours prior to the completion of high- intensity exercise tolerance in Day-5. The systolic BP and mean arterial pressure levels were significantly lower (p < 0.05), following 5-day PEG supplementation, compared to the pre-supplementation (PRE; no supplement) and PLA condition, but not diastolic BP. In addition, exhaled hydrogen sulphide (eH2S) was significantly greater (p < 0.05) following PEG, compared to PRE and PLA condition. Although PEG did not significantly alter time-to-exhaustion in intense constant load exercise (p = 0.11), the results indicate substantial improvements (~6%) in 8 out of 12 participants. Blood [glucose] was lower during constant-load exercise (p < 0.05) but no changes in blood [lactate]. In this study, for the first time the BP-lowering effect of PEG supplementation was reported, and this vasorelaxant effects likely related to enhanced bioavailability of hydrogen sulphide (H2S). Additionally, there was appreciable inter-subject variability in the response of PEG on exercise tolerance which requires further study to elucidate the factors that influence its ergogenic potential.